2010
DOI: 10.1121/1.3298437
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual assessment of quality of urban soundscapes with combined noise sources and water sounds

Abstract: In this study, urban soundscapes containing combined noise sources were evaluated through field surveys and laboratory experiments. The effect of water sounds on masking urban noises was then examined in order to enhance the soundscape perception. Field surveys in 16 urban spaces were conducted through soundwalking to evaluate the annoyance of combined noise sources. Synthesis curves were derived for the relationships between noise levels and the percentage of highly annoyed (%HA) and the percentage of annoyed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
162
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(194 citation statements)
references
References 14 publications
14
162
1
1
Order By: Relevance
“…Thus, they have been rejected from the analysis. If water sound sources are active factors when one focuses on specific locations such as parks or open squares [40], [41], this effect can probably be neglected when considering very contrasted sound environment at a district scale. …”
Section: Participant and Study Session Variabilitymentioning
confidence: 99%
“…Thus, they have been rejected from the analysis. If water sound sources are active factors when one focuses on specific locations such as parks or open squares [40], [41], this effect can probably be neglected when considering very contrasted sound environment at a district scale. …”
Section: Participant and Study Session Variabilitymentioning
confidence: 99%
“…Among researchers there is also no clear consensus yet regarding the soundscape terminology and choices of bipolar adjectives [19,20,[23][24][25][26]. In particular, the issues arise in the selection criteria for bipolar adjectives used, which is accompanied by the question of universal applicability due to loss of certain semantic nuances in translation and determining proper statistical approach.…”
Section: Introductionmentioning
confidence: 99%
“…There are also other studies that have shown that people especially enjoy the sound of water 6 . In that sense, we can conclude that the real challenge is how to create an enjoyable soundscape in nowadays overpopulated cities.…”
Section: Astesj Issn: 2415-6698mentioning
confidence: 99%
“…So far soundscape research has been oriented mainly on evaluating a soundscape in a qualitative way, e.g. assessing the soundscape pleasantness or rather its unpleasantness [6]- [9]. In order to describe a certain soundscape in greater detail and provide a more comprehensive approach to soundscape research, it is necessary to use other methods which could also define soundscape characteristics quantitatively.…”
Section: Introductionmentioning
confidence: 99%